Prognostic and Clinical Significance of COX-2 Overexpression in Laryngeal Cancer: A Meta-Analysis - Du, Jingwei; Feng, Jun; Luo, Deyan; Peng, Lijuan (Frontiers in Oncology, 2022)
Objective: Several studies were conducted to explore the clinical significance of cyclooxygenase-2 (COX-2) overexpression in laryngeal cancer. However, the associations between COX-2 overexpression and clinicopathological characteristics of laryngeal cancer patients remained unclear. Here, we performed a meta-analysis to evaluate the role of COX-2 overexpression in the risk, clinical progression, and prognosis of laryngeal cancer. Methods: The eligible literature was obtained from PubMed, Embase, Web of Science, and China national knowledge infrastructure (CNKI) databases. Odds ratio (OR), risk ratio (RR), and 95% confidence interval (CI) were calculated to assess the strength of the associations, and I2 statistics were used to evaluate heterogeneity among studies. Publication bias was detected with Begg’s test and Egger’s test. Results: A total of 47 eligible articles were included for the meta-analysis after screening. COX-2 expression levels in the laryngeal cancer patients were significantly higher than that in the normal controls (OR = 11.62, 95% CI: 6.96 – 19.40, P < 0.05). The pooled results also showed that there were significant correlations between COX-2 overexpression and clinicopathological characteristics (Tumor stage, OR = 3.26, 95% CI: 2.13 – 4.98, P < 0.05; Lymph node metastasis, in Asians, OR = 2.35, 95% CI: 1.53 – 3.60, P < 0.05; Recurrence, OR = 10.71, 95% CI: 3.54 – 32.38, P < 0.05; T stage, in Asians, OR = 2.52, 95% CI: 1.66 – 3.83, P < 0.05.). In addition, significant correlations between COX-2 overexpression and overall survival of laryngeal cancer were found both in Asians and in Caucasians (Total, HR = 1.73, 95% CI: 1.23 – 2.24, P < 0.05; Survival in Asians, HR = 2.59, 95% CI: 1.27 – 3.92, P < 0.05; Survival in Caucasians, HR = 1.59, 95% CI: 1.03 – 2.14, P < 0.05.). Conclusions: The results of the meta-analysis suggested that COX-2 overexpression was significantly associated with the increased risk, worse clinicopathological progression, and poorer prognosis of laryngeal cancer.